Pengaruh insentif pajak dan layanan pajak terhadap persepsi dan kepatuhan wajib pajak - Sitorus, Riris Rotua; Tambun, Sihar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The Indonesian government provides tax incentives during Covid-19 and opens online and more intensive tax services, hoping to serve taxpayers well during Covid-19. This study aims to prove the effect of tax incentives and tax services on the perception and compliance of taxpayers (WP). Two models are tested: the development of tax incentives and benefits on taxpayer perceptions. Second, the impact of tax incentives, tax services, and taxpayer perceptions on taxpayer compliance. A sample of 300 respondents from the MSME sector who received the benefits of tax incentives and services during covid 19 in Jakarta. Analysis using structural equation modeling. The results prove that tax services are established to impact taxpayer perceptions. Then, tax incentives, tax services, and taxpayer perceptions are proven to affect taxpayer compliance—tax services indirectly on taxpayer compliance through taxpayer perceptions. The results of this study recommend that the priority strategies to improve taxpayer compliance are improving tax services, education, and socialization to taxpayers so that they have a good perception of taxes and, finally, providing tax incentives.